Peranan Kalsium dan Vitamin D Dalam Penanganan Osteoporosis, Pencegahan Fraktur Patologis, Serta Korelasi Terhadap Pandemi COVID-19 - Brilliant Citra Wirashada; Maya Rahmayanti Syamhadi; Sulis tiawan (Universitas Muhammadiyah Surabaya, 2020)
AbstractOsteoporosis remains a very significant public health problem, causing high morbidity andmortality rates. Vitamin D deficiency (<50 nmol / L) is a worldwide epidemic with multipleimplications for human health. Inadequate serum 25-hydroxyvitamin D (25 (OH) D)concentrations are associated with muscle weakness, decreased physical performance, and anincreased likelihood of falls and fractures. Various studies have shown that higher serum 25(OH) D levels (at least 700 IU of vitamin D, especially cholecalciferol) will reduce theincidence of fractures. The problem of osteoporosis has been exacerbated by the COVID-19pandemic. As well known, COVID-19 is a respiratory tract infection caused by the new SARSCoV-2 virus. In general, this pandemic has caused deterioration of the economic and healthcare systems in many countries. Under difficult circumstances, recent research has shown thatoptimizing blood levels of vitamin D offers a solution that promises to reduce the risk of deathfrom COVID-19 infection. This literature review was aimed to discuss the role of calcium andvitamin D in the management of osteoporosis, pathological fractures (brittle fractures), andCOVID-19.Keywords: osteoporosis, vitamin D, COVID-19